The Effect of Gamification on Customer Loyalty Vidio Dot Com (Survey on Vidio Arcade Users of the Vidio Dot Com Application) - Fitriani, Dena; Muttaqin, Zaenal; Dai, Ratna Meisa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to explore the effect of gamification implementation on customer loyalty on Over the Top (OTT) service platforms, specifically Vidio Dot Com. The OTT industry in Indonesia is growing rapidly with various major players such as Netflix, Disney+ Hotstar, and Vidio. Vidio Dot Com utilizes a gamification strategy through the Vidio Arcade feature to increase customer loyalty amid fierce competition. This research uses a quantitative descriptive method with a sample of 96 respondents who are active users of Vidio Dot Com. The findings revealed a strong and significant correlation between the use of gamification and customer loyalty, where gamification contributed 63.5% to customer loyalty. Fun experiences and reward incentives are the main factors that drive user engagement. Thus, gamification is proven to be an effective marketing tool in increasing customer loyalty on OTT platforms. This research also recommends further development of gamification elements to increase user engagement and maintain customer loyalty.